Sequentially mediated effects of weight-related self-stigma and psychological distress in the association between perceived weight stigma and food addiction among Taiwanese university students: a cross-sectional study - Huang, Po-Ching; Lee, Chiu-Hsiang; Griffiths, Mark D.; O’brien, Kerry S.; Lin, Yi-Ching; Gan, Wan Ying; Poon, Wai Chuen; Hung, Ching-Hsia; Lee, Kuo-Hsin; Lin, Chung-Ying (Springer Science and Business Media LLC, 2022)
Background: Weight-related stigma has negative physiological and psychological impacts on individuals’ quality of life. Stigmatized individuals may experience higher psychological distress and therefore increase the potential risk to develop obesity and/or food addiction. The present study examined the associations and mediated effect between perceived weight stigma, weight-related self-stigma, and psychological distress in explaining food addiction among Taiwanese university students. Methods: All participants (n = 968) completed an online survey which included the Perceived Weight Stigma Questionnaire, Weight Self-Stigma Questionnaire, Depression, Anxiety, Stress Scale-21, and Yale Food Addiction Scale Version 2. Results: After controlling for demographic variables, significant associations were found in the paths from (1) perceived weight stigma to weight-related self-stigma (β = 0.23), psychological distress (β = 0.35), and food addiction (β = 0.23); (2) weight-related self-stigma to psychological distress (β = 0.52) and food addiction (β = 0.59); and (3) psychological distress to food addiction (β = 0.59) (all p-values < 0.001). The mediation model showed the sequential mediated effect of weight-related self-stigma and psychological distress in the association between perceived weight stigma and food addiction. Conclusions: The results provide novel insights that weight-related self-stigma and psychological distress sequentially mediated the relationship between perceived weight stigma and food addiction among Taiwanese university students. The findings of the present study could be implemented into interventions that aim to reduce food addiction derived from weight-related stigma. Future studies should consider group analysis to consider confounding factors or other populations to provide more evidence regarding the mechanism of weight-related stigma.